Analysis of puerperal metritis treatment records in a grazing dairy farm in Argentina - de la Sota, Rodolfo Luzbel; Corva, Santiago; Dominguez, German; Madoz, Laura Vanina; Jaureguiberry, Maria; Giuliodori, Mauricio (Tierärztliche Praxis Ausgabe G: Großtiere / Nutztiere, 2020)
Objective To assess the efficacy of antibiotic usage for the treatment of puerperal metritis (PM) and its association with reproductive performance, a retrospective cohort study including a total of 9168 records of cows from a dairy farm in Argentina was run.Material and methods Cows having a PM3 (metricheck, scale 0–3) and treated with ceftiofur (ceftiofur crystalline free acid, 6.6 mg/kg) at 0–21 days postpartum (p. p.) (n = 2688), and cows having a PM 1–2 and not treated with an antibiotic at 0–21 days p. p. (n = 6480) were included in the study. All cows were reexamined with metricheck to assess the clinical cure (vaginal discharge [VD] score 0), partial cure (VD score similar or lower than previous), no cure (VD score higher than previous). Cows with a metricheck VD1–3 after 0–21 days p. p. were diagnosed as clinical endometritis (CE) 1–3. The occurrence of PM1–3, cure rate, calving to conception interval, the hazard of pregnancy, odds for non-pregnancy, and odds for CE were analyzed using SAS software.Results A total of 8876 PM1–3 records were included, 2435 records of PM3 treatments with ceftiofur (27.43 %), and 6441 records of PM1–2 (72.57 %) with no treatment. Cows having PM1 and PM2 became pregnant 14 and 12 days earlier than cows with PM3 (p < 0.001). The PM3 ceftiofur treated cows had a clinical cure of 24.85 % (PM0); 53.63 % had a partially cure; and 18.52 % no cure. Conversely, cows with PM1–2 had a 51.96 %, 20.70 %, and 24.53 % cure rate, respectively (p < 0.001). Cows having complete cure became pregnant 13 and 11 days earlier than cows having partial cure and no cure (p < 0.001). Cows that had PM3 during the first 21 days p. p. had twice the chances of developing CE compared to cows having PM1–2 (41.28 % vs. 24.14 %, p < 0.001). After 21 days p. p., less than 1 % of cows with clinical cure developed CE compared to 63.32 % that developed CE with partial cure, and 38.21 % with no cure (p < 0.001).Conclusion and clinical relevance After ceftiofur treatment, 78 % of cows were cured when measured by disappearance of fetid VD but only 25 % of cows had clinical cure when measured by appearance of a clear VD. The cows that remained with clinical metritis had more chances of having CE after 21 days p. p. and had more days open than cows with clear normal VD.
Keywords: Uterus; dairy cow; ceftiofur; treatment efficacy; antimicrobial resistance